Time above range for predicting the development of type 2 diabetes - Alejandra Marco; Alejandra Marco; Marcos Pazos-Couselo; Marcos Pazos-Couselo; Jesús Moreno-Fernandez; Ana Díez-Fernández; Manuela Alonso-Sampedro; Manuela Alonso-Sampedro; Carmen Fernández-Merino; Carmen Fernández-Merino; Arturo Gonzalez-Quintela; Arturo Gonzalez-Quintela; et al. (Frontiers Media S.A., 2022)
AimTo investigate the prognostic value of time range metrics, as measured by continuous glucose monitoring, with respect to the development of type 2 diabetes (T2D).Research design and methodsA total of 499 persons without diabetes from the general population were followed-up for 5 years. Time range metrics were measured at the start and medical records were checked over the period study.ResultsTwenty-two subjects (8.3 per 1,000 person-years) developed T2D. After adjusting for age, gender, family history of diabetes, body mass index and glycated hemoglobin concentration, multivariate analysis revealed 'time above range' (TAR, i.e., with a plasma glucose concentration of >140 mg/dL) to be significantly associated with a greater risk (OR = 1.06, CI 1.01-1.11) of developing diabetes (AUC = 0.94, Brier = 0.035).ConclusionsTime above range provides additional information to that offered by glycated hemoglobin to identify patients at a higher risk of developing type 2 diabetes in a population-based study.